The Effect of Media Use of Comic Without Text ond Direct Learning on Early Knowledge and Narrative Writing Skills For Grade IV Elementary School Students - Maryani Maryani; Syahrul R; Darnis Arief; Budi Setiawan (International Journal of Educational Dynamics, 2019)
This study aims to reveal the Effect of Media Use of Comics Without Text and Direct Learning on Early Knowledge and Narrative Writing Skills for Grade IV Elementary School Students. The type of research used is Quasi Experiment in the form of Randomized Control Group Only Design. The population in this study were fourth grade students of SDN Gugus V District X Koto Tanah Datar District with a sample of fourth grade students at SDN 26 Singgalang and fourth grade students at SDN 30 Singgalang. Sampling is done by Simple Random Sampling technique. The technique of analyzing data through initial knowledge tests, and the final test of narrative writing skills. The hypothesis is proposed using the t-test formula and two-way ANOVA. The results of the study showed that there was an effect of the use of media comics without text and direct learning on the initial knowledge and writing skills of students in elementary school fourth grade with 1) tests of narrative writing skills of students learning using comic media without text higher than students learning using learning directly with the average in the experimental class 83.37 and the average in the control class 76.75, 2) the test of narrative writing skills of students with high initial knowledge who learn using comic media without text higher than those who learn using direct learning with the average in the experimental class 85.75 and the average in the control class 79.64, 3) the test of narrative writing skills of students with low initial knowledge who learn using comic media without text is higher than those who learn using direct learning with on average in experimental class 81 and average in class control 75.19, 4) there is no interaction between comic media without text and the initial knowledge of students on narrative writing skills with ftable 4.09 and fcount 0.547.